Tools of justice : non-discrimination and the Indian Constitution - Kannabirān, Kalpana (Routledge, 2012)
In the years since independence, the Indian subcontinent has witnessed an alarming rise in violence against marginalized communities, with an increasing number of groups pushed to the margins of the democratic order. Against this background of violence, injustice and the abuse of rights, this book explores the critical, 'insurgent' possibilities of constitutionalism as a means of revitalising the concepts of non-discrimination and liberty, and of reimagining democratic citizenship. The book argues that the breaking down of discrimination in constitutional interpretation and the.